The Ethics of Tax Lawyering - Hatfield, Michael (Open textbook library., 2013)
This chapter's objective is to raise interesting tax ethics issues in practical contexts. There are 43 notes and questions to prompt and guide discussions, and primary source materials to inform the discussions (e.g., cases, IRC provisions, and Circular 230 excerpts). These Teaching Notes flesh out the notes and questions, summarize the cases, and provide additional information and suggestions for readings. Of course, the ultimate test for casebook materials lies in student interaction based on the materials, so I assigned the materials to my students, and, taking their reaction into account, I have made suggestions below as to materials to eliminate or emphasize in customizing for your own class. Faculty materials also available: In addition to the free, open learning materials for students listed above, this eLangdell chapter includes a teacher's manual. Faculty and staff at CALI member schools can access this and other faculty-only materials by logging in to eLangdell with their cali.org username and password. Contact CALI if you have questions.